Conization and lymph node evaluation as a fertility-sparing treatment for early stage cervical cancer. Issue 3 (March 2021) - Martinelli, Fabio; Ditto, Antonino; Filippi, Francesca; Vinti, Daniele; Bogani, Giorgio; Leone Roberti Maggiore, Umberto; Evangelista, Mariateresa; Signorelli, Mauro; Chiappa, Valentina; Lopez, Salvatore; Somigliana, Edgardo; Raspagliesi, Francesco
Abstract : Introduction: To evaluate oncological and obstetrical outcomes of early stage cervical cancer patients who underwent conservative management to retain childbearing potential. Methods: Data of women (aged <40 years) who underwent fertility sparing treatment for International Federation of Gynecology and Obstetrics (FIGO) stage IA1 with lymphovascular invasion (LVSI) and IB1 cervical cancer were prospectively collected. All patients underwent cervical conization/s and laparoscopic nodal evaluation (pelvic lymphadenectomy/sentinel node mapping). Oncological and obstetrical outcomes were assessed. Results: Overall, 39 patients met inclusion criteria; 36 (92.3%) women were nulliparous. There were: 3 (7.7%) IA1-LVSI+; 11 (28.2%) IA2; and 25 (64.1%) IB1 cervical cancers, according to 2018 FIGO stage classification. Histological types were 22 (56.4%) squamous carcinoma and 17 (43.6%) adenocarcinoma. Pelvic lymphadenectomy was performed in 29 (74.4%) patients, while 10 (25.6%) patients had only sentinel node mapping. In 4 (10.3%) patients conservative treatment was discontinued due to nodal involvement and 2 (5.1%) patients requested definitive treatment (hysterectomy) after a negative lymph node evaluation. Among 33 (84.6%) patients who retained their childbearing potential, 17 (51.5%) had a second conization. 2 (6.1%) patients relapsed and underwent definitive treatment. After a median follow-up of 51 months (range 1–184) no deaths were reported. 22 (70.9%) patients attempted to conceive. There were 13 natural pregnancies among 12 (54.5%) women who got pregnant. Live birth rate was 76.9%: 9 (69.2%) term and 1 (7.7%) preterm (at 32 weeks) deliveries. 2 (15.4%) miscarriages (first and second trimester) and 1 (7.7%) termination of pregnancy for medical reasons were recorded. Conclusion: Conization plus laparoscopic nodal evaluation may be a safe and feasible conservative option in the setting of fertility-sparing treatment for early-stage cervical cancer patients.